Sosialisasi Demam Berdarah Dengue (DBD) dan Pencegahannya pada Siswa SMA Negeri 4 Manado - Jasman; Semuel Layuk; Syamsu Alam; Anselmus Kabuhung (CV. CENDIKIA JENIUS INDONESIA, 2024)
Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus, transmitted through the bites of Aedes aegypti mosquitoes. Environmental factors play a significant role in the emergence of outbreaks, particularly in Manado City, which has a high population density and intense community mobility. Insufficient health education among students leads to a lack of understanding regarding DHF. To address this issue, an outreach program was conducted to provide accurate information. This initiative aimed to enhance students' knowledge about DHF and its prevention strategies, utilizing lecture and discussion methods at SMA Negeri 4 Manado. The outreach activity involved a community service team and university students, with 51 students and accompanying teachers participating. The results indicated a notable increase in students' understanding of DHF prevention. It is recommended that all students and teachers at SMA Negeri 4 Manado actively engage in cleaning the school environment to eliminate mosquito breeding sites and prevent the spread of this disease. This outreach is expected to empower students as agents of change in promoting personal and community health.